Leveraging the clinical collaborative model to drive value improvement. Issue 4 (July 2018) - Luckenbaugh, Amy N.; Auffenberg, Gregory B.
Abstract : Purpose of review: Physician-led quality improvement collaboratives have emerged across surgical disciplines as a means to measure and subsequently improve the quality and cost of care. In this review, we will provide an overview of recent successes within quality improvement collaboratives, as well as discuss future opportunities for such initiatives. Recent findings: Successful quality improvement collaboratives have coupled data registries with a collegial environment to achieve data-driven improvements in care across diverse practice settings. Such efforts have a track record for accomplishing specific patient safety gains, and have more recently addressed complex care scenarios where data and consensus building have been leveraged to clarify optimal care pathways. Collaboratives are currently exploring mechanisms to meaningfully impact increasingly complex elements of care delivery, such as individual surgeon performance. Summary: Quality improvement collaboratives are in a unique position to understand patterns in care across populations, lead evidence-based assessments of variation in quality, and to attempt to intervene to improve outcomes based on the data they accumulate. As healthcare increasingly shifts to emphasize quality of care, physician-led collaboratives represent an important mechanism to drive improvement.